Heparin-based, injectable microcarriers for controlled delivery of interleukin-13 to the brain. (4th September 2020) - Schirmer, Lucas; Hoornaert, Chloé; Le Blon, Debbie; Eigel, Dimitri; Neto, Catia; Gumbleton, Mark; Welzel, Petra B.; Rosser, Anne E.; Werner, Carsten; Ponsaerts, Peter; Newland, Ben
Abstract : The anti-inflammatory cytokine IL-13 can be loaded and released from heparin-based cryogel biomaterials for sustained delivery to the brain. Abstract : Interleukin-13 (IL-13) drives cells of myeloid origin towards a more anti-inflammatory phenotype, but delivery to the brain remains problematic. Herein, we show that heparin-based cryogel microcarriers load high amounts of IL-13, releasing it slowly. Intra-striatal injection of loaded microcarriers caused local up-regulation of ARG1 in myeloid cells for pro-regenerative immunomodulation in the brain.